Embryogenic competence of microspores is associated with their ability to form a callosic, osmoprotective subintinal layer - Rivas-Sendra, Alba (Journal of experimental botany, 2019)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology.